Syndromic Surveillance: Adapting Innovations to Developing Settings - Chretien, Jean-Paul; Burkom, Howard S; Sedyaningsih, Endang R; Larasati, Ria P; Lescano, Andres G; Mundaca, Carmen C; Blazes, David L; Munayco, Cesar V; Coberly, Jacqueline S; Ashar, Raj J; Lewis, Sheri H (PLoS medicine, 2008)
The tools and strategies of syndromic surveillance, say the authors, hold promise for improving public health security in developing countries.